Acute symptomatic seizures secondary to myelin oligodendrocyte glycoprotein antibody‐associated disease. Issue 12 (14th October 2022) - Montalvo, Mayra; Khattak, Jamal F.; Redenbaugh, Vyanka; Britton, Jeffrey; Sanchez, Cristina Valencia; Datta, Abhigyan; Tillema, Jan‐Mendelt; Chen, John; McKeon, Andrew; Pittock, Sean J.; Flanagan, Eoin P.; Dubey, Divyanshu
Abstract: Objective: To report the clinical presentations and outcomes of patients with seizure and myelin oligodendrocyte glycoprotein antibody–associated disease (MOGAD). Methods: We retrospectively reviewed the electronic medical records for clinical and paraclinical features among patients with seizures and MOG‐IgG (immunoglobulin G) seropositivity. Results: We identified 213 patients with MOG‐IgG seropositivity who fulfilled criteria for MOGAD. Seizures attributed to central nervous system (CNS) autoimmunity were observed in 10% of patients ( n  = 23: 19 children, 4 adults). The majority ( n  = 19, 83%) had pediatric disease onset. Focal motor seizures were the most common seizure semiology (16/23; 70%). Focal to bilateral tonic‐clonic seizures were present in 12 patients (53%), and 3 patients (13%) developed status epilepticus. All patients had features of encephalitis at onset of seizures. Cerebral cortical encephalitis (CCE) was the most common radiological finding (10 unilateral and 5 bilateral cases). Eight of 23 patients (35%) had only CCE, six of 23 patients (26%) had only acute disseminated encephalomyelitis (ADEM), and seven of 23 patients (30%) had features of both. Fifteen patients (65%) had leptomeningeal enhancement. Three patients (13%) had coexistence of N ‐methyl‐d ‐aspartate receptor (NMDAR) IgG. Only 3 of 23 patients (13%) developed drug‐ resistant epilepsy. Although the majority had MOGAD relapses (14/23, 60%) had only 5 of 23 patients had recurrence of episodes of encephalitis with associated seizures. Twenty‐one of 23 patients (91%) had seizure freedom at last follow‐up. Significance: MOG‐IgG evaluation should be considered in patients who present with encephalitis and focal motor and/or focal to bilateral tonic‐clonic seizures, especially pediatric patients with magnetic resonance imaging (MRI) brain findings consistent with CCE, ADEM, or other MOGAD presentations. The majority of these seizures are self‐limited and do not require maintenance/chronic antiseizure medications. Although seizure recurrence is uncommon, many patients have MOGAD relapses in the form of encephalitis and optic neuritis.